Macroeconomic and Institutional Determinants of Non-Performing Loans in Nepalese Commercial Banks - Kami, Dilip Kumar; Acharya, Dipendra Raj; Dutta, Kaushal; Bhatt, Nilam; Bist, Nirajan; Bista, Nar Bahadur (Nepalese Journal of Economics, 2025)
This study examines the macroeconomic and institutional determinants of non-performing loans in Nepalese commercial banks. Non-performing loan and total loan and advances are the selected dependent variables. The selected independent variables are bank size, capital adequacy ratio, interest rate, gross domestic product, inflation rate and money supply. The study is based on secondary data of 16 commercial banks with 128 observations for the study period from 2016/17 to 2023/24. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB), Economic Survey Report, World Bank Data and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of the macroeconomic and institutional determinants on non-performing loans in Nepalese commercial banks. The study showed that inflation rate has a positive impact on non-performing loan. It indicates that increase in inflation rate leads to increase in non-performing loan. In contrast, capital adequacy ratio has a negative impact on non-performing loan. It indicates that increase in capital adequacy ratio leads to decrease in non performing loan. Similarly, money supply has a negative impact on non-performing loan. It indicates that increase in money supply leads to decrease in non-performing loan. Likewise, interest rate has a negative impact on non performing loan. It indicates that higher the lending interest rate, lower would be the non-performing loan. Further, gross domestic product has a negative impact on non-performing loan. It indicates that increase in gross domestic product leads to decrease in non-performing loan. However, bank size has a positive impact on non-performing loan. It indicates that larger the bank size, higher would be the non-performing loan.